2009
DOI: 10.1002/anie.200804529
|View full text |Cite
|
Sign up to set email alerts
|

A Spin‐Crossover Cluster of Iron(II) Exhibiting a Mixed‐Spin Structure and Synergy between Spin Transition and Magnetic Interaction

Abstract: How low can you go? An Fe(II) (4) square was prepared by self-assembly and exhibits both thermally induced and photoinduced spin crossover from a system with four high-spin (HS) centers to one with two high-spin and two low-spin (LS) centers. The spin-crossover sites are located on the same side of the square, and the spin transition and magnetic interactions (see picture) are synergistically coupled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(84 citation statements)
references
References 45 publications
1
78
0
3
Order By: Relevance
“…3; Supplementary Table 3). In both configurations, the grid had a cis-2HS-2LS configuration, abbreviated as [(HS-Fe II ) 2 (LS-Fe II ) 2 ], similar to that described in the first crystallographically determined 2HS-2LS iron grid and the subsequent theoretical studies thereupon 33,34 , although more recently a trans-2HS-2LS grid has also been reported 35 . Increasing the measurement temperature from 100 K to 190 K caused the c axis to double in length, and the unit cell to contain two crystallographically independent sites, both of which were occupied by two overlaid cluster configurations (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 66%
“…3; Supplementary Table 3). In both configurations, the grid had a cis-2HS-2LS configuration, abbreviated as [(HS-Fe II ) 2 (LS-Fe II ) 2 ], similar to that described in the first crystallographically determined 2HS-2LS iron grid and the subsequent theoretical studies thereupon 33,34 , although more recently a trans-2HS-2LS grid has also been reported 35 . Increasing the measurement temperature from 100 K to 190 K caused the c axis to double in length, and the unit cell to contain two crystallographically independent sites, both of which were occupied by two overlaid cluster configurations (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 66%
“…7,8 Short-range correlations may also compete with long-range interactions and give rise to deviation from mean-field behaviors, 9 as evidenced in some cases by distinctive long relaxation tails from the LIESST state. 10 Although the vast majority of thermal spin transitions proceed in a single step, there has been an increasing number of two-step transitions reported for polymeric, [11][12][13][14][15][16][17] polynuclear, [18][19][20][21][22][23][24] or mononuclear SCO systems. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Such transitions result most frequently from the existence of two crystallographically (symmetrically) independent SCO Fe I I sites with slightly different coordination environments, leading to dissimilar transition temperatures delimiting a plateau (or shoulder), which usually occurs with an approximately equal populations of HS and LS species.…”
Section: Imentioning
confidence: 99%
“…The presence of additional hydrazide group allows preparation of dihydrazones. Despite the fact that mono-and bis-(thio)carbohydrazides are also known to chelate iron, [19][20][21][22][23][24][25] which make them potential RR inhibitors, there are only few investigations published where their anticancer activities were explored, [25][26][27][28][29][30][31][32][33] with no study about their possible mechanism of action.…”
mentioning
confidence: 99%